General Social Survey, 1972-2012 (Cumulative File) - Smith, Tom W. ([Verlag nicht ermittelbar], 2013)
The General Social Surveys (GSS) were designed as part of a data diffusion project in 1972. The GSS replicated questionnaire items and wording in order to facilitate time-trend studies. The latest survey, GSS 2012, includes a cumulative file that merges all 29 General Social Surveys into a single file containing data from 1972 to 2012. The items appearing in the surveys are one of three types: Permanent questions that occur on each survey, rotating questions that appear on two out of every three surveys (1973, 1974, and 1976, or 1973, 1975, and 1976), and a few occasional questions such as split ballot experiments that occur in a single survey. The 2012 surveys included seven topic modules: Jewish identity, generosity, workplace violence, science, skin tone, and modules for experimental and miscellaneous questions. The International Social Survey Program (ISSP) module included in the 2012 survey was gender. The data also contain several variables describing the demographic characteristics of the respondents.